Measuring and Evaluating Supply Chain Management Performance of a Company Using the Scor Method - Sekarjati, Bella Devi; Pribadi, Firman; Nuryakin, Nuryakin (Interdisciplinary Social Studies, 2022)
The problem with IUP SUMANTO is that it has n   systematically taken performance measurements with a particular model. The supply of materials in the form of mined sand has problems so it experiences delays and also has an impact on shipping to sand depots to consumers. With this problem, the performance of Supply Chain Management (SCM) is considered not optimal, so research is needed to measure its performance from the company's supply chain. This study aims to measure the performance of Supply Chain Management (SCM) using the Supply Chain Operation Reference (SCOR) method in order to optimize every activity in the company's SCM. The research was conducted with a qualitative approach through direct observation, interviewing company experts along with filling out special questionnaires and documentation. Performance measurement will focus on five core processes, namely Plan, Source, Make, Deliver, and Return. There are 18 indicators studied with indicators that have the attributes of Reliability, Responsiveness, Agility. The method used in this study is the Analytical Hierarchy Process (AHP) method which is used to obtain weighting results so that the performance assessment is more precise. The final value is obtained by multiplying the performance value with the weight of importance. This research was conducted at a sand mining company in Yogyakarta. The results of this study indicate that the performance of SCM in the sand mining company is in the good category with a final performance rating of 77.05 from a scale of 0 to 100. For indicators that have a low performance rating below 70, suggestions for improvement will be given. One of the proposed improvements is to provide training and certification to employees. The company is expected to be able to make improvements according to the suggestions given based on the research that has been done.